2021
DOI: 10.3390/ijerph18083870
|View full text |Cite
|
Sign up to set email alerts
|

Movement Patterns in Students Diagnosed with ADHD, Objective Measurement in a Natural Learning Environment

Abstract: Attention deficit hyperactivity disorder is the most common neuropsychological disorder in childhood and adolescence, affecting the basic psychological processes involved in learning, social adaptation and affective adjustment. From previous research, the disorder is linked to problems in different areas of development, with deficiencies in psychological processes leading to the development of the most common characteristics of the disorder such as inattention, excess of activity and lack of inhibitory control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…Reduced globus pallidus volume in ADHD patients has been reported in several previous ADHD studies (Frodl and Skokauskas, 2012;Hoogman et al, 2017). The pallidum regulates voluntary movement (Gillies et al, 2019); specifically, hyperkinesia is among the pronounced characteristic symptoms in ADHD patients (Sempere-Tortosa et al, 2021); that is, damage to the pallidum, as shown in this study, implicates movement disorder. Also, the correlation analysis indicating a positive relationship between the right pallidum and disease severity; implied that the higher the reduction of gray matter volume in the right pallidum, the higher the disease severity.…”
Section: Structural Differences In Adhdsupporting
confidence: 77%
“…Reduced globus pallidus volume in ADHD patients has been reported in several previous ADHD studies (Frodl and Skokauskas, 2012;Hoogman et al, 2017). The pallidum regulates voluntary movement (Gillies et al, 2019); specifically, hyperkinesia is among the pronounced characteristic symptoms in ADHD patients (Sempere-Tortosa et al, 2021); that is, damage to the pallidum, as shown in this study, implicates movement disorder. Also, the correlation analysis indicating a positive relationship between the right pallidum and disease severity; implied that the higher the reduction of gray matter volume in the right pallidum, the higher the disease severity.…”
Section: Structural Differences In Adhdsupporting
confidence: 77%
“…Few studies have used a noncontact method, such as Kinect, to record the amount of movement in patients with ADHD. Their results revealed significant differences in the amount of objective movement between participants with ADHD and a control group [42,43]. The present study is the first to use OpenPose to objectively analyze body movements in patients with ADHD before and after medication in the consulting room.…”
Section: Discussionmentioning
confidence: 70%
“…It is also possible to analyze participants’ behavior in their natural environment. For example, recently, Sempere-Tortosa et al observed that the amount of movement of children with ADHD in class is significantly higher than that of their peers without this disorder in almost all joints captured with Kinect [ 67 ].…”
Section: Discussionmentioning
confidence: 99%